Tax evasion in the informal sector in the Kumasi Metropolis - Okine, Benedict Nii Ayi (KNUST, 2025)
A Thesis Submitted To Department Of Accounting And Finance In Partial Fulfillment Of The Requirements For The Degree Ofmaster Of Business Administration (Finance Option)